Investigating the effect of childhood socioeconomic background on interpersonal trust: Lower childhood socioeconomic status predicts lower levels of trust. (15th July 2019) - Stamos, Angelos; Altsitsiadis, Efthymios; Dewitte, Siegfried
Abstract: Trust is the foundation of human relationships, therefore, understanding its determinants is of utmost importance. In line with recent findings we predict that one factor influencing the individual levels of trust is childhood socioeconomic background. Childhood socioeconomic background has been found to be a key determinant of various behaviors in adulthood as it directs individuals to adopt specific large clusters of behavioral traits often referred to as life-history strategies. In two studies, we show that childhood socioeconomic background is associated with social trust through the adoption of different life-history strategies. In the first study, we establish the link between childhood socioeconomic background and trust and we show that the relationship is mediated by the adoption of different life-history strategies. In the second study, we analyze the data of General Social Survey to replicate the finding in a large sample and provide some initial evidence of two potential moderators of the relationship, sense of control and resource scarcity.